ANTI-ANTIOXIDANT ACTIVITY LEAVES ANANASA COMOSUS IS MEDIUM USING THE DPPH METHOD - Hesti Marliza; alfin_surya; Fitri Harlina Sagala; Zaiyar; Eliya Mursyida (JURNAL KATALISATOR, 2024)
One of Indonesia's best fruit plants, the pineapple (Ananas comosus), has a high antioxidant content. Ananas comosus, or pineapple leaves, are a component of the pineapple plant. They have slightly thick leaf sheaths with tiny brown thorns pointing upward at their margins. (Ananasa comosus). The purpose of this study is to investigate the pineapple (Ananas comosus) leaf's potential as a natural antioxidant source. The DPPH technique is being utilized in a descriptive quantitative research study to investigate the antioxidant capacity of pineapple leaves. Ananas comosus, or dried and crushed pineapple leaves, were macerated in methanol solvent until the sample was completely submerged. The IC50 value ascertained by the linear regression equation is the parameter employed in this technique. After the extract has evaporated from the solvent, its absorbance is measured at 520 nm using a microplate reader and the DPPH technique. Pineapple leaves show moderate antioxidant activity against DPPH with an IC50 value of 113.069 ppm, according to data from calculations and study. According to this study, the antioxidant capacity of pineapple leaves (Ananas comosus) is moderate.